Level of Land Adjustment Durian (Durio zibethinus Murr.) in District Sigumpar District Toba - Sidabukke, Simon Haholongan; Harahap, Fitra Syawal; Kurniawan, Dedi (JURNAL AGROPLASMA, 2024)
Utilization of land for other uses in Sigumpar District needs to be supported by information regarding land suitability. Therefore, an evaluation of the characteristics of the level of land suitability in the area was carried out, to analyze improvement efforts aimed at increasing productivity, as well as to create a map of actual land suitability and potential land suitability for durian plants in the district. The method used is the survey method. Land units are based on soil maps, slope maps, altitude maps, land cover maps, consisting of 6 land units and 18 points. The analysis method is the comparing (matching) method. The results of the research show that the level of land suitability for durian plants (Durio zibethinus Murr.) The actual land conditions suitable for durian cultivation in Sigumpar District are 1,856.22 ha. (2) Potential land conditions suitable for durian cultivation in Sigumpar District are 1,726.22 ha. Where limiting factors that cannot be remedied are temperature and soil texture, while limiting factors such as nutrient retention, nutrient availability, water availability and erosion hazards can be remedied in the form of: (1). Liming and fertilization adjusted to the results of soil tests on the land. Making drainage channels, planting parallel to contours, and making terraces. Keywords: land suitability evaluation, durian plant, utilizzation of other area, subdistrict of Sigumpar